PEMBERDAYAAN KELOMPOK WANITA TANI (KWT) MELALUI OPTIMALISASI KEBUN TOGA DAN PRODUKSI TELUR ASIN DI NAGARI SIALANG GAUNG KABUPATEN DHARMASRAYA - Ediset - Ediset; Amrizal Anas; Nurhayati Nurhayati; Syofyan Syofyan (Jurnal Hilirisasi IPTEKS, 2024)
Women Farmers Group can play a role in rural development, because most of the FWG members are housewives who still have a lot of time, energy and can utilize vacant land and home gardens as locations to run relevant businesses to be more productive. Increased productivity of FWG members will be able to help the household economy so that in turn it can make them more empowered. The problem is that efforts to help the household economy are sometimes hampered by limited knowledge and skills. In order for the quality of human resources FWG to be adequate, it is necessary to conduct training activities through a structured extension program. The objectives of the activity are 1) to educate FWG Nagari Silga members in utilizing empty land into a Family Medicinal Plant garden and 2) to increase knowledge and skills in making salted eggs for FWG members in Nagari Sialang Gaung, Koto Baru District, Dharmasraya Regency. The method of transferring knowledge and technology (science and technology) applied is using the extension method with a lecture, training and mentoring approach. The results of the activity are the Women Farmers Group in Nagari Sialang Gaung, Dharmasraya Regency has increased knowledge and skills in utilizing empty land to be more productive with evidence that a 120 meter Toga garden (10 x 12 meters) has been established which contains 10 (ten) types of medicinal plants and has been able to produce new food products in the form of salted eggs. The conclusion of the activity is that the transfer of science and technology has been able to increase the productivity of FWG members, especially in utilizing vacant land and producing salted egg products, which indicates that they will be more empowered in the future.